2023
DOI: 10.3389/fgene.2023.1256627
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel locus C2 controlling canary yellow flesh color in watermelons

Girim Park,
Durre Shahwar,
Gaeun Jang
et al.

Abstract: The flesh color of watermelon is an important trait that is determined by carotenoid composition and affects consumers’ fruit desirability. Although a complete dominant control by C locus (Cllcyb) for canary yellow flesh (CY) over red flesh has been reported, red and CY colors frequently appear as a mixed pattern in the same flesh (incomplete canary yellow, ICY) in F1 and inbred lines carrying dominant C alleles. Therefore, we examined the genetic control of the mixed color pattern in ICY using whole-genome re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…A QTL analysis in melon (Cucumis melo) identi ed a PPR gene (CmPPR1) as the candidate gene for the esh phenotype, and this locus represents one of the two signi cant loci that control fruit esh color in melon(Galpaz et al 2018). A recent genetic mapping study showed that the C 2 locus controlling yellow esh color in watermelon is cosegregated with the marker derived from a PPR gene, indicating a vital role of PPR genes in regulating fruit color in diverse species(Park et al 2023). In the current study, we have identi ed 12 PRR gene isoforms associated with either of the color spaces in the study.…”
mentioning
confidence: 99%
“…A QTL analysis in melon (Cucumis melo) identi ed a PPR gene (CmPPR1) as the candidate gene for the esh phenotype, and this locus represents one of the two signi cant loci that control fruit esh color in melon(Galpaz et al 2018). A recent genetic mapping study showed that the C 2 locus controlling yellow esh color in watermelon is cosegregated with the marker derived from a PPR gene, indicating a vital role of PPR genes in regulating fruit color in diverse species(Park et al 2023). In the current study, we have identi ed 12 PRR gene isoforms associated with either of the color spaces in the study.…”
mentioning
confidence: 99%